Ray Tracing Acceleration Algorithm Based on FaceMap - Jian Wang (Mathematical Problems in Engineering, 2022)
Raster method and ray tracing are two important algorithms in computer graphics. The former, raster method, marked by high speed and efficiency, has the disadvantage of an unrealistic rendering effect. By contrast, ray tracing requires considerable computing resources and time despite its advantages of high fidelity and simple structure, thus only suitable for offline rendering. Given such limitations, a ray-tracing acceleration algorithm that combines the raster method and ray tracing is proposed in this study based on FaceMap, a two-dimensional data structure that stores surface distribution under point light or the view of a camera. Firstly, all triangular surfaces of the 3D model are rasterized by linear surface projection to form the surface distribution of a spherical panorama. Secondly, the structure of FaceMap is adopted to store the distribution information of all the surfaces in the scene. Thirdly, the data on the intersecting surfaces in this direction are collected by projecting the ray onto FaceMap in the ray-tracing process, thus reducing the intersection and propagation operations and improving the efficiency. Four object models including chessboard, grass patch, bust, and typewriter are selected for comparative rendering experiments. Our proposed method is used to compare with Rhino and VRay rendering software, respectively. The results show that our proposed method obtained better rendering effects within greatly reduced rendering time (© 2018Optical Society of America).